Doxycycline Degradation by the Oxidative Fenton Process - Alexandre A. Borghi; Milena F. Silva; Saleh Al Arni; Attilio Converti; Mauri S. A. Palma (Journal of Chemistry)
Doxycycline is a broad-spectrum tetracycline occurring in domestic, industrial, and rural effluents, whose main drawback is the increasing emergence of resistant bacteria. This antibiotic could be degraded by the so-called Fenton process, consisting in the oxidation of organic pollutants by oxygen peroxide (H2O2) in the presence of Fe2+. Experiments were performed according to an experimental Rotational Central Composite Design to investigate the influence of temperature (0–40.0°C), H2O2 concentration (100–900 mg/L), and Fe2+ concentration (5–120 mg/L) on residual doxycycline and total organic carbon concentrations. Whereas the final residual doxycycline concentration ranged from 0 to 55.8 mg/L, the oxidation process proved unable to reduce the total organic carbon by more than 30%. The best operating conditions were concentrations of H2O2 and Fe2+ of 611 and 25 mg/L, respectively, and temperature of 35.0°C, but the analysis of variance revealed that only the first variable exerted a statistically significant effect on the residual doxycycline concentration. These results suggest possible application of this process in the treatment of doxycycline-containing effluents and may be used as starting basis to treat tetracycline-contaminated effluents.